The effect of the mtDNA4834 deletion on hearing - Kong, Wei-Jia; Hu, Yu-Juan; Wang, Qiong; Wang, Ying; Han, Yue-Chen; Cheng, Hua-Mao; Kong, Wen; Guan, Min-Xin (Biochemical and biophysical research communications, 2006)
Mutations in mitochondrial DNA (mtDNA) are associated with diverse pathological states in humans, notably sensorineural deafness. In humans, mtDNA4977 deletion, known as common deletion, is thought to play a critical role in presbyacusis. A similar mtDNA deletion occurs in the naturally aging rats is mtDNA4834 deletion. Today, it is still obscure about the effect of common mtDNA deletion on the presbyacusis and hearing loss. We establish a model of rat associated with mtDNA4834 deletion in inner ear by d-galactose. It was found that the malondialdehyde (MDA) increased with superoxide dismutase (SOD) decreasing in the inner ear of the rat treated with d-galactose than of the control. However, there was no significant difference in elevation of ABR threshold between the rat with mtDNA4834 deletion induced by d-galactose and control. After aminoglycoside antibiotic injected, the hearing threshold of the rats carrying mtDNA4834 deletion increased significantly compared with the rats without mtDNA4834 deletion. The results show that resembled accelerated aging in the inner ear of the rat could be induced by injecting d-galactose. Moreover, those suggest that mtDNA4834 deletion can not directly induce the hearing loss, but acting as a predisposing factor which can greatly enhance the sensitivity of the inner ear to the aminoglycoside antibiotic.